BLOOD PRESSURE EFFECTS OVER TIME OF BIPOLAR RADIOFREQUENCY RENAL DENERVATION IN UNTREATED HYPERTENSION. (April 2021) - Weber, Michael; Kirtane, Ajay; Weir, Matthew; Leon, Martin
Abstract : Objective: It is believed that interruption of the renal nerves which lie in close proximity to the renal arteries, will effectively reduce blood pressure. As a first step, this study measured the blood pressure effects of ablating these nerves using radiofrequency energy produced by a bipolar catheter positioned into each renal artery in untreated hypertensive patients. Design and method: REINFORCE was a randomized, sham-controlled multicenter trial. Patients with office systolic blood pressure (SBP) of 150–180 mmHg and average 24-hour ambulatory SBP of 135–170 mmHg after medication washout underwent bipolar radiofrequency renal denervation or a sham procedure. The planned outcome was 8-week change in 24-hour ambulatory SBP. Enrollment was terminated for apparent futility before a sufficient sample for powered efficacy comparisons was enrolled, although patient observation continued. Safety assessments included all-cause death, renal failure, severe hypotension/syncope, hypertensive crisis, and renal artery stenosis. Results: Baseline 24-hour BP was 148.3 ± 10.9/85.7 ± 9.1 mmHg for the denervation group (N = 34, age 58.5 ± 10.1 years, 47% female) and 149.1 ± 7.2/86.4 ± 9.8 mmHg for the control group (N = 17, age 58.2 ± 9.8 years, 24% female). At 8 weeks, mean 24-hour SBP reductions for the renal denervation and control groups were 5.3 mmHg (95%CI -8.8, -1.8) and -8.5 mmHg (95%CI -13.3, -3.8), respectively (difference 3.3 [95%CI -2.8, 9.3]; p = .30). Antihypertensive medications could then be added. By 6 months, decreases in SBP were greater for the denervation group, yielding between-group differences of -7.2 (95%CI -15.2, 0.8; p = .08), -9.7 (95%CI -17.7, -1.7; p = .02), and -11.4 (95%CI -19.2, -3.7; p < .01) for 24-hour, daytime ambulatory, and office measurements, respectively. Control rates (office SBP < 140) were higher in the denervation group both at 6 months (52% vs. 12%, p < 0.01) and 12 months (42% vs. 13%, p = 0.048). Medication use was similar in both groups. By 12 months, one denervation patient had a hypertensive urgency and one experienced progression of renal artery stenosis. Conclusions: The antihypertensive effects of renal denervation can be delayed for weeks following the procedure, but then appear to be sustained for at least 12 months.